Pola Perdagangan Global pada Perusahaan-Perusahaan Berteknologi Tinggi - Sari, Dyah Wulan; Restikasari, Wenny (Jurnal Ekonomi dan Pembangunan Indonesia, 2021)
This study deals with firm level data of Indonesian high-tech manufacturing industries to determine firm’s production, especially among global trade variables, such as export intensity, vertical trade integration, and two-way trade. This study employs a generalized method of moments (GMM) approach to examine the most important factors of a global trade phenomenon. In the full-sample, the result demonstrates that vertical trade integration and two-way trade are significant determinants on firm’s production while export intensity is not. In ordinary trader sub-sample, export intensity is a significant determinant of firm’s production, whereas in vertical trader sub-sample export intensity is not.